Ministry of Finance Decree No. 46 of the Year 2018 Concerning the Customs Procedures to be followed for the Release of the Machinery, Equipment and Tools Required for Exercising the Activity Licensed for the Projects inside the Technological Zones = وزارة المالية قرار رقم 46 لسنة 2018 فى شأن الإجراءات الجمركية التى يتعين إتباعها للإفراج عن الآلات والمهمات والأدوات والمهمات اللازمة لمزاولة النشاط امرخص به للمشروعات داخل المناطق التكنولوجية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic